Validity and Short-Term Repeatability of a Novel Hand-Held Respiratory Health Meter for the Assessment of Dynamic Maximal Respiratory Pressures in Healthy Young Adults - Ryynänen, Herkko; Sovijärvi, Anssi; Kuronen, Ilpo; Ahokas, Essi; Valtonen, Maarit; Ihalainen, Johanna; Multanen, Juhani (Medical devices (Auckland, N.Z.), 2025)
Measuring maximal airway pressure is an essential part of the assessment of respiratory functions. Portable handheld devices have made clinical measurements more available, but reliable and user-friendly devices for non-clinical use remain rare. This study sought to determine the validity and short-term repeatability of measurements of dynamic maximal inspiratory pressure (dMIP) and dynamic maximal expiratory pressure (dMEP) by using a novel self-administered respiratory health meter (WellO2-RHM) in asymptomatic young adults. dMIP and dMEP were measured with WellO2-RHM in asymptomatic adult volunteers (n=26, 15 male and 11 female, age 26-41 years). These values were compared with quasi-static maximal inspiratory pressure (MIP) and maximal expiratory pressure (MEP) obtained from the same volunteers using another respiratory manometer (MicroRPM). The measurements of dMIP and dMEP with WellO2-RHM were repeated in the same individuals at an interval of one week for assessment of their short-term repeatability. The Pearson correlation coefficients of dMIP and dMEP values with MIP and MEP values were high (r=0.840, p<0.001; r=0.849, p<0.001, respectively). The dMIP and dMEP values were consistently lower than the quasi-static MIP and MEP values in the same individuals. The short-term repeatability of the dMIP and dMEP in one week interval proved to be moderately good in terms of the coefficient of variation (CV), the intraclass correlation coefficient (ICC), the standard error of measurement (SEm) and minimal detectable change (MDC) (10.0%, 0.825, p<0.001, 7 cmH2O and 20 cmH2O and 9.1%, 0.895, p<0.001, 12 cmH2O and 34 cmH2O, respectively). The results indicate that the WellO2-RHM is a valid and repeatable method for the assessment of dMIP and dMEP in asymptomatic young adults, but the absolute values are lower than those obtained with devices measuring quasi-static MIP and MEP. The findings suggest that WellO2-RHM can be used for self-monitoring of the effects of respiratory muscle training in healthy young adults.